Asymptotische Eigenschaften einer analytischen im Halbebene Funktion - Strelitz, S. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш.И. Стрелиц. Асимптотические свойства функции, аналитической в полуплоскостиŠ. Strelicas. Analizinių funkcijų pusplokštumėje asimptotinės savybės